Oseltamivir resistance among influenza viruses: surveillance in northern Viet Nam, 2009-2012 - Nguyen Thi Kim Phuong; Nguyen Le Khanh Hang; Nguyen Co Thach; Hoang Vu Mai-Phuong; Le Quynh Mai (World Health Organization Regional Office for the Western Pacific, 2013)
Introduction: Antiviral resistance has been reported in seasonal influenza A viruses and avian influenza A(H5N1) viruses in Viet Nam, raising concerns about the efficacy of treatment. Methods: We analysed specimens from two sources during the period 2009-2012: influenza-positive samples from influenza-like illness patients at sentinel clinics in northern Viet Nam and isolates from patients with confirmed A(H5N1) infections. Pyrosequencing was used to detect mutations: H275Y [for A(H1N1) and A(H5N1)], E119V [for A(H3N2)] and I117V [for A(H5N1)]. A neuraminidase inhibition assay was used to determine the Inhibitory Concentration 50 (IC50) values for all influenza A and B isolates. Results: There were 341 influenza A positive samples identified; influenza A(H1N1)pdm09 was identified most frequently (n = 215). In 2009, oseltamivir resistance was observed in 100% (19 of 19) of seasonal A(H1N1) isolates and 1.4% (3/215) of A(H1N1)pdm09 isolates. This H275Y mutation was not found in influenza subtypes A(H5N1) or A(H3N2) isolates. Discussion: In Viet Nam, seasonal and A(H5N1) influenza vaccines are not currently available; thus, effective treatment is required. The presence of oseltamivir-resistant viruses is therefore a concern. Active surveillance for oseltamivir resistance among influenza viruses circulating in Viet Nam should be continued.